2001
DOI: 10.1152/ajpendo.2001.281.4.e857
|View full text |Cite
|
Sign up to set email alerts
|

Absence of cardiac lipid accumulation in transgenic mice with heart-specific HSL overexpression

Abstract: Hormone-sensitive lipase (HSL) hydrolyzes triglyceride (TG) in adipose tissue. HSL is also expressed in heart. To explore the actions of cardiac HSL, heart-specific, tetracycline (Tc)-controlled HSL-overexpressing mice were generated. Tc-responsive element-HSL transgenic (Tg) mice were generated and crossed with myosin heavy chain (MHC)alpha-tTA Tg mice, which express the Tc-responsive transactivator (tTA) in the heart. The double-Tg mice (MHC-HSL) were maintained with doxycycline (Dox) to suppress Tg HSL. Upo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
40
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 29 publications
3
40
0
Order By: Relevance
“…Exercise training does not affect the expression of HSL protein in muscle, but decreases the sensitivity of stimulation of muscle HSL activity by epinephrine (78). Heart-specific transgenic overexpression of HSL prevents the accumulation of cardiac triglyceride normally seen in fasted rodents (79). In addition, heart-specific overexpression of HSL alters the expression of cardiac genes for fatty acid oxidation, transcription factors, signaling molecules, cytoskeletal proteins, and histocompatibility antigens.…”
Section: Musclementioning
confidence: 99%
“…Exercise training does not affect the expression of HSL protein in muscle, but decreases the sensitivity of stimulation of muscle HSL activity by epinephrine (78). Heart-specific transgenic overexpression of HSL prevents the accumulation of cardiac triglyceride normally seen in fasted rodents (79). In addition, heart-specific overexpression of HSL alters the expression of cardiac genes for fatty acid oxidation, transcription factors, signaling molecules, cytoskeletal proteins, and histocompatibility antigens.…”
Section: Musclementioning
confidence: 99%
“…To explore the pathophysiological function of activated HSL in the development of diabetic cardiomyopathy, we planned to induce diabetes in the tetracycline-inducible, heart-specific HSL-overexpressing mice that we generated in a previous study (40). However, inducible HSL expression declined with increasing generations.…”
Section: Characterization Of Heart-specific Hsl-overexpressing Micementioning
confidence: 99%
“…Since heart expresses HSL, cardiac HSL might be expected to be activated in diabetes; however, there are a limited number of studies investigating the function and regulation of cardiac HSL in diabetes. In a previous study we generated transgenic (Tg) mice with tetracycline-inducible HSL overexpression in heart and reported that Tg mice lacked fasting-induced TAG accumulation in cardiomyocytes (40). In the current study we have sought to clarify the pathophysiological functions of cardiac HSL in the development of diabetic cardiomyopathy by using Tg mice with constitutive overexpression of HSL in the heart.…”
mentioning
confidence: 99%
“…Conditional TG expression using a tetracycline-regulated system (tet system), has been widely used to study the roles of numerous genes in the heart (4,7,14,22,23,26,31,32,39,40). The main advantage of the tet system is its versatility: it offers the possibility of activating or inactivating TG expression by turning on or off a transactivator (TA) by adding or withdrawing tetracycline in the animal diet.…”
mentioning
confidence: 99%
“…Transactivation of a responsive promoter placed upstream of the TG of interest by tet-off (tTA) or tet-on (rtTA) is inhibited or enhanced, respectively, by tetracycline, which prevents (tTA) (8) or permits (rtTA) (11,35) binding to the corresponding promoter. One of the tetracyclines most commonly used in this system is doxycycline (Dox) (14,22,23,26,31,32,39,40), which is added to the drinking water or chow. Therefore, the most appropriate control animals for TG expression in this system are double transgenic mice in their repressed state (ϩDox in the tet-off system and ϪDox in the tet-on system), which are compared with double transgenic mice in their activated state (ϪDox in the tet-off system and ϩDox in the tet-on system).…”
mentioning
confidence: 99%